AN INTERESTING CASE OF CMV RETINITIS IN A PATIENT OF ALL ON MAITENANCE THERAPY - PAWAN KUMAR SINGH; Manoranjan Mahapatra; TULIKA SETH; PRAVAS MISRA; PRADEEP VENKATESH; VINEET SEHGAL (Mediterranean Journal of Hematology and Infectious Diseases)
A 45 years old male, known case of T-cell Acute Lymphoblastic Leukemia on maintenance therapy presented with painless progressive dimunition of vision in both eyes. Evaluation revealed Cytomegalovirus retinitis with low CD4 counts. CMV retinitis is usually seen in HIV disease or in post allogenic stem cell transplant recipietn patients. CMV retinitis occuring in ALL maintenance phase is very rare. The patient showed some improvement with intra-vitreal and intra-venous Gancyclovir injections.